(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Endophytes are set against pathogenic substances and therefore asymptomatically invade plants. As is shown, however, endophytic fungi may act differently under diverse biotic and abiotic conditions where the host plant can also play a defining role. The genetic differences between an endophytic fungus and a pathogenic fungus may be substantially different. However, endophytic fungi have often been isolated throughout the years and in different host plants they never produce disease signs.